Optimizing Personnel Services: Analysis of the Effectiveness of e-HR Integration for Civil Servant Leave Management in Gubeng District, Surabaya - Kulsum Eka Mimin Mubaiyanah; Ika Devy Pramudiana; Aris Sunarya; Sapto Pramono (International Journal of Humanities and Social Sciences Reviews, 2025)
This study explores the implementation of an electronic Human Resource Management System (e-SDM) in the Gubeng sub-district of Surabaya to optimize civil servant (PNS) leave management. The primary focus is on assessing how digitalization improves efficiency, transparency, accountability, and service quality in human resource administration, particularly in leave processing. Traditionally, manual procedures required 7-14 days to approve leave requests, involved multiple steps, manual calculations, and were prone to errors, delays, and lack of transparency. The introduction of the e-SDM system significantly reduces processing time to approximately one day, enabling online submission, real-time monitoring, and electronic approval accessible anytime and anywhere via smartphones. The system automatically calculates leaves balances and prevents over-application, ensuring data accuracy and reducing misuse. Besides operational efficiency, the system enhances transparency by providing accessible real-time status updates, creating an audit trail for each decision, and making the process auditable and accountable. Despite these advantages, challenges such as user resistance, digital literacy, infrastructure issues, and system integration remain. This research employs descriptive-analytical methods, combining interviews, observations, and documentation, to analyze the effectiveness of e-SDM implementation. The findings indicate that digitalization has streamlined leave management, minimized administrative burdens, and improved data accuracy. Moreover, it fosters a fairer and more transparent work environment, reinforcing good governance principles and supporting Surabaya's vision to become a smart city. The research underscores the importance of technological adaptation within bureaucratic reforms and offers strategic recommendations for further system improvements. Overall, the successful adoption of e-SDM in Gubeng serves as a model for digital transformation in public service delivery, contributing to more efficient, transparent, and accountable governance in local government institutions.